Management of animal bites and rabies prophylaxis [Hayvan isiriklarina yaklaşim ve kuduz profilaksisi] - (:unkn) unknown (My University, 2002)
Animal bites have been characterized as an "unrecognized epidemic" because of their frequency, preventability, and potential severity. Bite wounds are common and often mistakenly considered innocuous by both patients and physicians. Most data on the incidence of infection, bacteriology, and various medical and surgical methods of treatment come from small studies. Bite wounds consist of lacerations, evulsions, punctures, and scratches. Although 80% of patients never seek and do not need medical care, awareness of the magnitude of the infectious complication from bites in growing.